Leksyka religijna w nazewnictwie miejscowym woj. kijowskiego i czernihowskiego w XVII i XVIII wieku - Pluskota, Teresa (Acta Polono-Ruthenica, 2008)
The subject of religious toponymy of the investigated period was shown on the example of appellatives, Orthodox church names and most frequent Christian names. Terminology connected with Catholic Church and Orthodox Church has been analyzed to show Polish influence in the native lexicon.